101. Posterior Gastric Perforation After Blunt Abdominal Trauma in Geriatric Patient: A Rare Case - Tsurayya, Zulfa; Fauzie, Rayhan; Krislee, Andre; Waelauruw, Shania Quency Alexandra; Yani, Irhamna Syari (JBN (Jurnal Bedah Nasional), 2024)
Introduction : Blunt abdominal trauma commonly results from traffic accidents, with solid organ injuries being the most frequent. Gastric perforation, particularly of the posterior wall, is rare. We present the case of a 79-year-old male with a delayed diagnosis of posterior gastric perforation following blunt trauma. Case : A 79-year-old male, five days post-motorcycle accident, presented with severe abdominal pain and distension. He was fully conscious and hemodynamically stable. Physical examination revealed abdominal tenderness and guarding without external bruising. Radiography showed subdiaphragmatic free air, and hemoglobin was 11 g/dL. Exploratory laparotomy found 200 cc of free fluid, and a 1.5 cm full-thickness posterior gastric perforation near the prepyloric region was identified after opening the lesser sac. The perforation was closed with simple sutures. The patient developed pneumonia on day 6 postoperatively and was discharged on day 15 with uneventful recovery. Conclusions : Posterior gastric perforation following blunt trauma is uncommon but associated with high mortality. Early diagnosis and prompt surgical intervention are essential for improving prognosis.